MECHANICAL AND MORPHOLOGICAL PROPERTIES OF POLYAMIDE 12 COMPOSITE FOR POTENTIAL BIOMEDICAL IMPLANT: INJECTION MOLDING AND DESKTOP 3D PRINTER (Jurnal Teknologi (Sciences & Engineering), 2015)
Fused filament fabrication is a filament based rapid prototyping process, which offers the possibility of new polymer material for invention of biomedical implant. This study represents an investigation on a preparation and characterization of new polyamide 12 reinforced with 20 wt% of zirconium dioxide and hydroxyapatite by desktop 3D printer in comparison with conventional manufacturing method, injection molding. Polyamide 12 composite was compounded, pelletized and filament-extruded prior to apply to a 3D printer. Sample prototypes from the new polyamide composite have been successfully made and tested. Mechanical (flexural and impact) and morphological properties were evaluated and compared. From the results, the printed polyamide composite exhibited lower mechanical properties than injection molded due to the formation of porosity, laminate weakness and low pressure during printing. Although the mechanical properties of printed parts were lower than molded parts, but the capability of 3D printer to fabricate any customized 3D object could lead to the bright future and great contribution in this area, while at the same time many improvements can be made for the future works.